Growth and Stability Analysis of Lac Production in Madhya Pradesh, India (Indian Journal of Extension Education, 2022)
Lac is produced in different districts of Madhya Pradesh (MP), covering ten out of its eleven agro-climatic zones. This paper investigated the prospects of stakeholders from an assessment of the potential and performance of the state’s primary lac producing districts in Madhya Pradesh, India. Based on secondary data of lac production during Plans XI (2007-08 to 2011-12) and XII (2012-13 to 2016-17), data was evaluated crop by crop and district by district, and the trend was examined. Econometric measures, such as mean production, growth rate, and percent changes in mean value, were analyzed. Madhya Pradesh state that has contributed 13.66 per cent share during the XI plan has come down to 12.91 per cent during the XII plan. The state which recorded a negative growth rate to the extent of 30.15 per cent during the XI plan, reduced to 3.20 per cent during the XII plan. Chhindwara, Dindori and Mandla are the districts, which recorded decline growth during the XI plan but witnessed positive during the XII plan period. Data on crop-specific lac production were evaluated to determine less performing crops during these periods in the state. The state may initiate proper strategies to cope up with issues and problems of less performing districts.